1993
DOI: 10.1021/np50100a028
|View full text |Cite
|
Sign up to set email alerts
|

Two Bioactive Pterocarpans from Erythrina burana

Abstract: Bioactivity-directed fractionation of the CHCl3 extract of the bark of Erythrina burana afforded phaseollidin [1] and cristacarpin [2]. Both 1 and 2 exhibited moderate but selective activity towards DNA repair-deficient yeast mutants, whereas only 1 was found to be cytotoxic. 13C-nmr spectra of both compounds were assigned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…as established through HMBC correlations. The CD spectrum, which showed a positive Cotton effect at 315 nm and the negative optical rotation (½a 25 D ¼ À14:0) are consistent with the 6aR:11aR absolute configuration (Dagne et al, 1993), establishing 1 (erylysin A), as (6aR,11aR)-3 00 -hydroxy-2 0 ,2 0 -dimethylpyrano[6 0 ,5 0 :3,4]-2 00 ,2 00 -dimethyldihydropyrano[6 00 ,5 00 :9,10]pterocarpan ( Fig. 1).…”
Section: Resultssupporting
confidence: 61%
“…as established through HMBC correlations. The CD spectrum, which showed a positive Cotton effect at 315 nm and the negative optical rotation (½a 25 D ¼ À14:0) are consistent with the 6aR:11aR absolute configuration (Dagne et al, 1993), establishing 1 (erylysin A), as (6aR,11aR)-3 00 -hydroxy-2 0 ,2 0 -dimethylpyrano[6 0 ,5 0 :3,4]-2 00 ,2 00 -dimethyldihydropyrano[6 00 ,5 00 :9,10]pterocarpan ( Fig. 1).…”
Section: Resultssupporting
confidence: 61%
“…The antimicrobial activity previously observed with the genus Erythrina (Mitscher et al, 1988;Dagne et al, 1993) is confirmed by the remarkable effect of the roots of Erythrina vogelii against Gram-positive cocci as well as C. cucumerinum. Further work is underway in order to identify the active principles of E. vogelii.…”
Section: Discussionmentioning
confidence: 62%
“…The last one has previously been isolated from other species of the genus Erythrina, but not of E. velutina. On the other hand, it was the first time that homohesperetin has been isolated from a plant of the Fabaceae family (Dagne et al, 1993;Nkengfak et al, 1994;Tanaka et al, 1997). It was also already isolated five major alkaloids from the methanol extract of E. mulungu flowers.…”
Section: Introductionmentioning
confidence: 99%